Designating heritage as European: between the European Union's heritage initiatives and the nation-state. Issue 7 (10th November 2021) - Aceska, Ana; Mitroi, Ana-Roxana
ABSTRACT: In an attempt to foster its citizens' identification with Europe, the European Union has made a great effort to identify what can be called 'common European heritage'. Many heritage initiatives, centred around the idea that heritage should be designated as European by the member states' heritage sectors, have proven counterproductive – instead of reaching their goal to construct a more stable European identity, they served as repositories of national pride and tools in the negotiation of nationalist claims of the member states. Through the empirical case of the EU's own Maastricht Treaty and the peculiar ways it became 'common European heritage' within the Dutch state heritage sector, in this paper we analyze the discursive tactics of national policy makers and the power dynamics between national and EU heritage regimes in the process of designating heritage as European. We demonstrate that even EU states with more constitutional traditions like the Netherlands maintain a powerful role in the construction of heritage as an unchangeable set of traditions and values strictly defined within the national boundaries, lacking the mechanisms to change their state-sanctioned and firmly established ways of defining heritage as 'national' and to legitimatize EU heritage narratives.